24-Hour ICH Score Is a Better Predictor of Outcome than Admission ICH Score. (22nd October 2013) - Aysenne, Aimee M.; Albright, Karen C.; Mathias, Tiffany; Chang, Tiffany R.; Boehme, Amelia K.; Beasley, T. Mark; Martin-Schild, Sheryl
Abstract : Background . The ICH score is a validated tool for predicting 30-day morbidity and mortality in patients with intracerebral hemorrhage. Aims and/or Hypothesis . The aim of this study is to determine if the ICH score calculated 24 hours after admission is a better predictor of mortality than the ICH score calculated on admission. Methods . Patients presenting to our center with ICH from 7/08–12/10 were retrospectively identified from our prospective stroke registry. ICH scores were calculated based on initial Glasgow coma scale (GCS) and emergent head computed tomography (CT) on initial presentation and were recalculated after 24 hours. Results . A total of 91 patients out of 121 had complete data for admission and 24-hour ICH score. The ICH score changed in 38% from baseline to 24 hours. After adjusting for age, NIHSS on admission, and glucose, ICH score at 24 hours was a significant, independent predictor of mortality (OR = 2.71, 95% CI 1–19–6.20, andP = 0.018 ), but ICH score on admission was not (OR = 2.14, 95% CI 0.88–5.24, andP = 0.095 ). Conclusion . Early determination of the ICH score may incorrectly estimate the severity and expected outcome after ICH. Calculations of the ICH score 24 hours after admission will better predict early outcomes.